Floral biology and pollination strategy of Durio(Malvaceae) in Sarawak, Malaysian Borneo - Ng, Win Seng; Mohd Azlan Jayasilan, Abdul Gulam Azad; Wong, Sin Yeng (Society for Indonesian Biodiversity, 2020)
Ng WS, JayasilanMA, WongSY. 2020. Floral biology and pollination strategy of Durio(Malvaceae) in Sarawak, Malaysian Borneo.Biodiversitas 21:5579-5594.This study was carried out to investigate on the floweringmechanisms of four Duriospeciesin Sarawak. The anthesis startedin the afternoon(D. graveolensand D. zibethinus), evening (D. kutejensis) or midnight (D. griffithii); and lasted between 11.5 hours (D. griffithii) to 20 hours (D. graveolens). All four Duriospecies are generalists. Individuals of a fruitbat (Eonycteris spelaea, Pteropodidae) are considered as the main pollinator for D. graveolens, D. kutejensis,and D. zibethinuswhile spiderhunter (Arachnothera, Nectariniidae) is also proposed as a primary pollinator for D. kutejensis. Five invertebrate taxa were observed as secondary or inadvertent pollinators of Duriospp.: honeybee, Apis sp. (Apidae), stingless bee, Tetrigonasp. (Apidae), nocturnal wasp, Provespasp. (Vespidae), pollen beetle (Nitidulidae), and thrip (Thysanoptera). Honey bees and stingless beespollinated all four Duriospecies. Pollen beetles were found to pollinate D. griffithiiand D. graveolenswhile nocturnal wasps were found to pollinate D. kutejensisand D. zibethinus. Thrips were found to pollinate D. griffithiionly. Floral rewards include nectar, pollenand staminodes. The nectar productionof D. graveolens, D. kutejensis,and D. zibethinusincreased from the start of anthesis until just after midnight but decreased from then onwards. Duriogriffithiiproducedconsistent nectar concentration with inconsistent volume. Durio graveolens,D. griffithii, and D. zibethinusare partially self-incompatible